Simultaneous Production of High-Quality co2 and ch4 Via Multistage Process Using Chitosan-Based Membranes - Abejon-Elias, R (Elsevier B.V., 2023)
The use of biopolymers as membrane materials is a recent approach for reducing the environmental impact of CO2 separation processes. By considering previous process engineering tasks, it was concluded that no membrane currently provides sufficient purity and recovery to meet the requirements for the simultaneous direct separation of CO2 and CH4 in a single stage. The aim of this study is to simulate and optimise the separation of CO2 and CH4 from different sources using a simple multistage process, considering up to three stages. A chitosan biopolymer-based composite membrane with organic (ionic liquid) and different inorganic fillers in the selective layer was used to tune the selectivity and robustness of commercially available membranes. The process configuration utilized membrane units operating in series to enrich CO2 in the product stream from the permeate line, whereas the retentate line produced a CH4-enriched stream by mixing the retentate units of each stage. The target objectives were up to 95% purity and recovery of CO2 in the permeate outlet, corresponding to a recovery of CH4 higher than 97% in the retentate outlet stream of the multistage process. The decision variables included the permeance of each component, and thus the pair selectivity (CO2/CH4) and process-related parameters, such as the stage cut of each stage. Economic evaluation of the proposed three-stage separation process was performed for different process scales, from small installations to large plants. The total costs, the contribution of each term to the total costs, and the unitary costs were estimated for each operational scale, with reference to the feed flow rate based on the plant capacity. The lowest total cost was 0.3 € (Nm3)-1 for a large plant with a flow rate of 1000 Nm3 h−1. © 2023 The Author(s)